2021
DOI: 10.1039/d1nj03297f
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small FeS2 nanoparticles for highly efficient chemoselective transfer hydrogenation of nitroarenes

Abstract: Ultra-small FeS2 nanoparticles were prepared and used as catalysts in a hydrogen transfer reaction for the synthesis of substituted anilines. The catalytic performance is superior to current systems across all...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…DFT studies were also carried out to check the intrinsic catalytic performance of C-and N-covered Fe(110) surfaces for the hydrogenation of nitrobenzene to aniline and all the optimized structure are shown in Figure 18f, and it was observed that the nitrogen (N) surface sites can successfully trap nitrobenzene and aniline by coordination with phenyl rings via the formation of 3 C−N bonds, resulting in good catalytic activity. Recently, Southouse et al 140 prepared an ultrasmall FeS 2 NP ∼3−6 nm in size, using the solvothermal method for the hydrogenation of nitroarenes at 60 °C for 2 h. The reaction resulted in 100% conversion, 99% selectivity, and a low activation energy of ∼26.8 kJ mol −1 . Recently, in 2022, Meng et al 141 designed a Co-based catalyst dispersed on a hollow nanosphere (Co/HCS-800) for the same application at room temperature for 10−20 min with 99% conversion and selectivity.…”
Section: Ethanol and Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT studies were also carried out to check the intrinsic catalytic performance of C-and N-covered Fe(110) surfaces for the hydrogenation of nitrobenzene to aniline and all the optimized structure are shown in Figure 18f, and it was observed that the nitrogen (N) surface sites can successfully trap nitrobenzene and aniline by coordination with phenyl rings via the formation of 3 C−N bonds, resulting in good catalytic activity. Recently, Southouse et al 140 prepared an ultrasmall FeS 2 NP ∼3−6 nm in size, using the solvothermal method for the hydrogenation of nitroarenes at 60 °C for 2 h. The reaction resulted in 100% conversion, 99% selectivity, and a low activation energy of ∼26.8 kJ mol −1 . Recently, in 2022, Meng et al 141 designed a Co-based catalyst dispersed on a hollow nanosphere (Co/HCS-800) for the same application at room temperature for 10−20 min with 99% conversion and selectivity.…”
Section: Ethanol and Methanolmentioning
confidence: 99%
“…Non-noble transition-metal catalysts (Co, Ni, Fe etc.) have been readily utilized for the selective hydrogenation of nitro compounds. Huang et al reported cobalt-based catalysts supported on alumina (Co 3 O 4 /γ-MA) for the reduction of nitroarenes using N 2 H 4 ·H 2 O as a hydrogen source and ethanol as a solvent at 40 °C for 45 min with a yield of >99%. The catalyst was synthesized by one-pot hydrolysis of metal nitrates and combining it with 1,10-phenanthroline under N 2 atmosphere at 700 °C for 2 h. Cheong et al synthesized isolated iron single-atomic site catalyst supported on nitrogen-doped carbon (Fe 1 /N–C) for the hydrogenation of nitroarenes using hydrazine hydrate as a hydrogen source and EtOH as a solvent at 60 °C for 2 h. For the synthesis of Fe 1 /N–C catalyst, SBA-15 plays a crucial role of sacrificial agent.…”
Section: Various Hydrogen Sources For Cth Reactionsmentioning
confidence: 99%
“…Surfactants binding to specific facets can tailor the surface energy and induce anisotropic growth. For example, Cu 2‑x Se (cubic), Bi 2 S 3 (orthorhombic), and FeSe 2 (orthorhombic) tend to grow in 0D nanoparticles or in 1D NWs. McCarthy et al succeeded in synthesizing 2D Cu 2‑x Se, Bi 2 S 3 , and FeSe 2 NPs by using oleylamine as a surfactant (Figure b) . They reported that the amine groups in oleylamine form a secondary complex after being mixed with the metal or chalcogen precursors at an intermediate temperature.…”
Section: Solution-phase Synthesismentioning
confidence: 99%
“…Thus, a plethora of catalytic systems have been cleverly conceived and are associated with various reducing agents including hydrogen (H 2 ), hydrazine (N 2 H 4 ), hydrosilane (R 3 SiH), sodium borohydride (NaBH 4 ), and formic acid (HCOOH) . Unfortunately, even if some of these systems are quite effective, many of them show notable drawbacks including harsh reaction conditions, high catalyst loadings, long reaction times, the use of harmful organic solvents, flammable H 2 gas, high reaction temperatures, high-pressure equipment (autoclave), and relatively expensive and/or toxic metal catalysts and reagents. From this statement, the development of industrially transposable methodologies that offer milder and more environmentally friendly reaction conditions for the reduction of nitroarenes to anilines would be very useful. Moreover, azoaromatic compounds, which are generally secondary products formed during the formation of anilines, are extremely important in many areas of science.…”
Section: Introductionmentioning
confidence: 99%